Bridging epistemologies—Identifying uniqueness of lay and expert knowledge for agenda setting. (May 2019) - Gudowsky, Niklas; Rosa, Aaron
Highlights: Broad participation needed for responsible research and innovation policy agenda setting. Experts as well as lay-people deliver unique, yet compatible input for orienting future research and innovation. Expert-based studies are more detailed concerning specific future-relevant factors, trends, and emerging issues. Laypeople-based agenda setting focusses on contextualizing possible impacts on individuals and society. Abstract: Numerous foresight studies have been commissioned to address future R&I policies in the EU, spanning a variety of methodological approaches and scales of participation. Drawing out the discrepancy in content between expert- as well as citizen-based foresight studies, this article demonstrates that significant divisions exist between the resulting products with regard to informing policy creation. The Societal Challenges as declared by the European Commission provide an organizing framework for locating unique expert and citizen research topics within the context of knowledge generation towards specific policy ends. We link differences to the epistemological centers that organize both professional foresight research and citizen-based foresight projects. While professional foresight research institutions are more detailed in their examination of specificities concerning future-relevant factors, trends, and emerging issues, distinct qualitative differences emerge within citizen-based foresight initiatives with regard to contextualizing the possible impacts of future research and innovation projects.